The Effect of Human Resources Competency and Working Discipline on Patient Satisfaction in Konawe Regional General Hospital - Wahyuniati Hamid; Noval Nur; Asrip Putera (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to examine the empirical evidence of the influence of human resource competence and work discipline on patient satisfaction in the Konawe District General Hospital, to determine the effect of human resource competence on patient satisfaction at the Konawe District General Hospital, to determine the effect of work discipline on patient satisfaction at the Konawe District General Hospital. The design of this research is descriptive quantitative research with Explanatory research type. The population in this study were all inpatients at the Konawe General Hospital who had the consideration that patients staying at the hospital knew and felt the services provided by the hospital more than the outpatients, and the sample of this study was 100 inpatients. The analysis in this study is multiple linear regression. The results of this study indicate that Human Resources competence and work discipline have a positive and significant effect on Patient Satisfaction in the Konawe General Hospital. This means that Human Resources Competence and good work discipline together contribute to increasing patient satisfaction. Human Resources Competence has a positive and significant effect on Patient Satisfaction in Konawe General Hospital. This means that the better the Competency of Human Resources has contributed to the improvement of Patient Satisfaction in the Konawe General Hospital. Work discipline has a positive and significant effect on patient satisfaction in Konawe General Hospital. This means that good work discipline together contributes to the improvement of Patient Satisfaction in the Konawe General Hospital.